2023
DOI: 10.26689/jcer.v7i1.4547
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the Construction of “Double-Qualified” Teachers in Higher Vocational Colleges

Abstract: Vocational education is an important part of the overall education system. The development of higher vocational education is one of the guiding principles of education in China. The development of teachers is an important support for the development of vocational education. Teachers who can teach theoretically and guide students in practical work are known as “double-qualified” teachers. Building a highly qualified and professional double-qualified teaching team is the fundamental task in modernizing vocationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Through teachers’ regular interactions with enterprises, the linkage of vocational colleges and enterprises strengthens the construction of “double qualifications” for vocational teachers. According to the study by Wang et al. (2023) on constructing “double qualifications” teachers in higher vocational colleges, they suggest that vocational teachers should actively participate in various activities in enterprise to build a more professional teaching team.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through teachers’ regular interactions with enterprises, the linkage of vocational colleges and enterprises strengthens the construction of “double qualifications” for vocational teachers. According to the study by Wang et al. (2023) on constructing “double qualifications” teachers in higher vocational colleges, they suggest that vocational teachers should actively participate in various activities in enterprise to build a more professional teaching team.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Through teachers' regular interactions with enterprises, the linkage of vocational colleges and enterprises strengthens the construction of "double qualifications" for vocational teachers. According to the study by Wang et al (2023) on constructing "double qualifications" teachers in higher vocational colleges, they suggest that vocational teachers should actively participate in various activities in enterprise to build a more professional teaching team. In the process of participating in work-related learning through industry-university cooperation, work and learning adhere to the mutual benefit of both vocational colleges and enterprises in terms of vocational students' engagement in training.…”
Section: Teachers' Interactions With Enterprisesmentioning
confidence: 99%
“…However, from the actual situation, due to the influence of factors such as teaching pressure and difficulty, one-sided performance appraisal, limited number of establishments, and poor quality of students, the problems of a limited number of of teachers, large talent flow, and structural imbalance in vocational colleges is more prominent. In addition, due to the low scientific research expenses of teachers in vocational colleges, and the performance salary is linked to factors such as academic qualifications, professional titles, and class hours, improving professional titles has become the main way for teachers of all professions to improve their own treatment and improve their quality of life at this stage [2].…”
Section: Dilemma Of Professional Titlesmentioning
confidence: 99%
“…He suggested that universities should provide opportunities for young teachers to study in enterprises. Peng [11] argued that a high-level teacher team is an important guarantee for the development of higher education institutions. Previously, scholars have explored the career planning and development of teachers in vocational institutions from different dimensions.…”
Section: Research Statusmentioning
confidence: 99%